(untitled) (European Journal of Engineering Science and Technology, 2019)
The current paper described an experimental investigation about the effect of fiber orientation angle on the crashworthiness characteristics of carbon/epoxy fiber-reinforced composite pipes subjected to quasi-static axial compression. The samples, having three different fiber orientation angles as ± (40°), ± (55°) and ± (70°), were fabricated by filament winding technique. Crushing parameters, in terms of load-displacement response, load carrying capacity, energy absorption capability and mean crushing stress, were determined for each sample. The results showed that the fiber orientation angle was found to have significant influences on the crashworthiness of composite pipes. The increase in fiber orientation angle resulted with a decrease in energy absorption capability and an increase in crushing load efficiency. In the view of a specific energy absorption aspect, the minimum value of 32.20 J/g was obtained in ± (70°) fiber orientation and improvements up to 46% were achieved by increasing in orientation angle. Also, detailed investigations on fracture mechanisms were performed to understand failure modes. All samples were exhibited the progressive crushing in types of lamina bending or brittle fracturing.